Comparison of Haemorrhoidectomy Using Ligasure with Open (Milligan Morgan Haemorrhoidectomy) - Saman Naz, Ulas Khan, Hakim Jan, Nadir Saifullah Khan, Talat Shahzad, Muhammad Farooq, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare between haemorrhoidectomy using ligasure versus conventional haemorrhoidectomy in terms of operative time, bleeding and post-operative pain. Study design: Controlled randomized trial Place and duration of study: Department of Surgery, DHQ Hospital Abbottabad from 1stJuly 2018 to 31stDecember 2020 Methodology: One hundred and twenty patients were enrolled. Patients were allocated to two groups and haemorrhoidectomy done with ligasure (LS, group A) and conventional method i.e. Milligan Morgan haemorrhoidectomy (MMH, group B) and each group comprised 60 patients. In group A pedicals were coagulated with the ligasure rather than transfixed as in group B (MMH). Operative time and per operative bleeding recorded during surgery while postop pain score recorded using visual analogue score (0-10) especially during first defecation. Results: The mean age of 46±16.36 years were studied and 79.1% were males. In group A 72.5% patients were males and 27.5% females compared to 67.5% males and 32.5% females in group B. 87.5% of patients had 3rd degree hemorrhoids in group A while 89.4% had the same disease in group B. Operative time was between 20-35 minute in group A compared to 10-30minutes in group B. In group A 75% observed mild pain as recorded on VAS, 25% had moderate pain at time of first defecation while in group B 69.4% patients had moderate pain on VAS, 25.6% experienced mild pain and another 5% reported severe pain during defecation. Mean blood loss was 104.21±41.45 ml in both populations, in group A it was 83.59±34.34 ml while in group B it was 124.84±37.56 ml. Mean VAS of both populations was 3.55±2.05 while mean time of operation was 36.35±7.22.Using independent sample T test, there was statistically significant (P=0.000) difference on all three parameters between two groups. Conclusions: Haemorrhoidectomy using ligasure is safe and causes minimal bleeding, requires less operative time and is associated with less pain compared with conventional scissors dissection, and is a good alternative to diathermy excision.